Pressupostos para uma Teoria Penal na Filosofia do Direito de Hegel - Paula, Danielle Lima de (2019)
The present dissertation tries to undertake a hypothesis of interpretation of penal theory, based on the purpose of special prevention with the intention of understand in the work the Principles of Philosophy of Right of Hegel the penalty as promotion of